A de novo complete BRCA1 gene deletion identified in a Spanish woman with early bilateral breast cancer - Garcia-Casado, Zaida (BioMed Central, 2011)
BACKGROUND: Germline mutations in either of the two tumor-suppressor genes, BRCA1 and BRCA2, account for a significant proportion of hereditary breast and ovarian cancer cases. Most of these mutations consist of deletions, insertions, nonsense mutations, and splice variants, however an increasing number of large genomic rearrangements have been identified in these genes. METHODS: We analysed BRCA1 and BRCA2 genes by direct sequencing and MLPA. We confirmed the results by an alternative MLPA kit and characterized the BRCA1 deletion by Array CGH. RESULTS: We describe the first case of a patient with no strong family history of the disease who developed early-onset bilateral breast cancer with a de novo complete BRCA1 gene deletion in the germinal line. The detected deletion started from the region surrounding the VAT1 locus to the beginning of NBR1 gene, including the RND2, ΨBRCA1, BRCA1 and NBR2 complete genes. CONCLUSION: This finding supports the large genomic rearrangement screening of BRCA genes in young breast cancer patients without family history, as well as in hereditary breast and ovarian cancer families previously tested negative for other variations.